Academics’ career success at Malaysian research universities: a literature review - Abu Said, Al-Mansor; Tengku Abdul Jalal, Tengku Shahraniza; Mohd Rasdi, Roziah; Alias, Mazni; Sulaiman, Suzaimah (American-Eurasian Network for Scientific Information, 2015)
Background: The theories underpinning this study are based on three models: The Advanced Model of SCCT (Lent & Brown, 2006), Proactive Behaviour Model (Crant, 2000), and Integrated Models of Career Success (Barnett & Bradley, 2007). Objective: The purpose of this article is to develop a conceptual framework to measure academics’ career success at Research Universities. Results: Five factors are found to have potential influences on academics’ career success. The factors comprise of human capital factors, personality factors, person job-fit, personal and professional networking, and proactive behaviour. Additionally, this study projected that proactive behaviour mediates the relationship between personality and academics’ career success. Conclusion: The practical implications here are in terms of strengthening the HRD framework through organizational development, training and career development that can promote positive career outcomes.